Deteriorated function of cutaneous microcirculation in chronic congestive heart failure - Edvinsson, Marie-Louise (Science Press, 2011)
BACKGROUND: Chronic congestive heart failure is a complex condition that leads to dysfunction in the peripheral microcirculation. We have previously shown that vascular reactivity is reduced with increasing age. In this study, we examined a group of very old patients with severe chronic heart failure to test the hypothesis that vascular function is further compromised by a combination of heart failure and aging. METHODS: Cutaneous forearm blood flow was measured by laser Doppler flowmetry and compared among three groups: Group 1 (n = 20, mean ± SE: 85.5 ± 4 years), heart failure patients with New York Heart Association class IV (NYHA IV) and with a NT-proBNP level ≥ 5000 ng/L; Group 2 (n = 15, mean ± SE: 76.5 ± 2 years), heart failure patients with NYHA II and NT-proBNP ≤ 2000 ng/L, and Group 3 (n = 10, mean ± SE: 67.6 ± 3.0 years), healthy controls with no clinical signs of heart failure. The vasodilator response to the iontophoretic administration of acetylcholine (ACh), acting via an endothelial mechanism, and sodium nitroprusside (SNP), acting via a smooth muscle cell mechanism, were studied. RESULTS: All patients with heart failure had significantly reduced vascular reactivity independent of the mode of stimulation (ACh, SNP or heat) when compared to healthy controls. However, the responses did not differ between the two groups of heart failure patients. CONCLUSIONS: Cutaneous vascular reactivity is reduced in heart failure patients and does not correlate with the severity of the condition or age of patients.